Gender role analysis in achieving farmer household food security in Jember District - Fitrio Deviantony; Tantut Susanto (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Food security is a global issue that has received serious attention from various countries, including Indonesia. Indonesia still has problems related to gender inequality, which is a separate cause of food insecurity. This study aimed to analyze the mapping related to the food security of Jember farmers and its relation to household decision-making and the division of tasks related to food management in farming households. The study used a survey method by taking 251 samples of farming families from the working area of the Health Center in the Jember District. This study was conducted from May to July 2023. Data were collected using questionnaires and supported by qualitative data through in-depth interviews. Bivariate data analysis was performed using Spearman’s rho test. The results showed a correlation between gender identity and food security (p= 0,000), and there was a positive relationship pattern: the higher the gender role given, the more food security will increase in July (r= 0,504). In conclusion, there is a positive relationship between gender roles and food security; the higher the gender roles, the higher the farmers' food security.